Prostaglandin E‐major urinary metabolite diagnoses mucosal healing in patients with ulcerative colitis in remission phase. Issue 5 (14th February 2022) - Sakurai, Toshiyuki; Akita, Yoshihiro; Miyashita, Haruna; Miyazaki, Ryosuke; Maruyama, Yuki; Saito, Tomoko; Shimada, Mariko; Yamasaki, Takuji; Arhihiro, Seiji; Kato, Tomohiro; Matsuura, Tomokazu; Ikegami, Masahiro; et al.
Abstract: Background and Aim: Ulcerative colitis (UC) is usually detected by clinical symptoms, such as bleeding and diarrhea; however, it is rather difficult to assess during asymptomatic clinical remission (CR). Hence, there is a need for a biomarker that can reliably detect UC during remission. We previously reported on the utility of the prostaglandin E‐major urinary metabolite (PGE‐MUM) as a biomarker reflecting UC activity. In this study, we evaluated the effectiveness of the PGE‐MUM in the diagnosis of endoscopic, histological, and histo‐endoscopic mucosal remission of UC, comparing with fecal tests. Methods: This prospective study was conducted at the Jikei University Hospital between August 2017 and January 2021. Patients with UC in CR scheduled to undergo colonoscopy were included. The association between the PGE‐MUM with endoscopic remission (ER), histological remission (HR), and complete mucosal healing (CMH, defined as histo‐endoscopic remission) was analyzed. We also compared the area under the curve (AUC) for the receiver operating characteristic curves between PGE‐MUM, fecal calprotectin (FC), and fecal immunochemical test (FIT). Results: In total, 128 patients were analyzed. PGE‐MUM differed significantly in ER versus non‐ER (14.5 vs 16.7, P = 0.028), HR versus non‐HR (14.2 vs 17.4, P = 0.004), and CMH versus non‐CMH (14.3 vs 16.7, P = 0.021). There were no significant differences between the AUCs for PGE‐MUM, FC, and FIT for ER, HR, or CMH. Conclusions: The PGE‐MUM can determine CMH in UC even during CR, regardless of the disease phenotype, indicating its clinical benefit for non‐invasive monitoring.